2022
DOI: 10.1101/2022.01.11.475931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-genomic analysis of transcriptional modules across Salmonella Typhimurium reveals the regulatory landscape of different strains

Abstract: Salmonella enterica Typhimurium is a serious pathogen that is involved in human nontyphoidal infections. Tackling Typhimurium infections is difficult due to the species' dynamic adaptation to its environment, which is dictated by a complex transcriptional regulatory network (TRN). While traditional biomolecular methods provide characterizations of specific regulators, it is laborious to construct the global TRN structure from this bottom-up approach. Here, we used a machine learning technique to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…2b ). This iModulon has been enriched in almost all bacteria and archaea for which iModulons have been calculated ( 20 , 22 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…2b ). This iModulon has been enriched in almost all bacteria and archaea for which iModulons have been calculated ( 20 , 22 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in big data analytics have enabled the knowledge-enriched modularization of the transcriptome for various microbial species. 8,[11][12][13][14][15][16][17] Here we investigated if matched datasets of transcriptomes and proteomes could be modularized in the same way to reveal novel relationships between their compositions. Using ICA analysis of matched data sets we found that; 1) the modules of the proteome and the transcriptome are comprised of a similar list of gene products, 2) the modules in the proteome often represent combinations of modules from the transcriptome, 3) known transcriptional and post-translational regulation is reflected in differences between two sets of modules, allowing for knowledge-mapping when interpreting module functions, and 4) through statistical modeling, absolute proteome allocation can be inferred from the transcriptome alone.…”
Section: Discussionmentioning
confidence: 99%
“…10 iModulons could be knowledge-enriched, thus yielding a fundamental understanding of the composition of the transcriptome and how it changes between conditions. [11][12][13][14][15][16][17] ICA has now been applied to several organisms across the phylogenetic tree. 9 This advance led to discoveries of gene functions, 18 effects of mutations on protein complex regulation, 19 and identifying energetic trade-offs across sample conditions.…”
Section: Introductionmentioning
confidence: 99%
“…and genes involved in translation such as infA and fusA which encode translation initiation factor IF-1 and elongation factor G respectively(Figure 2b). This iModulon has been enriched in almost all bacteria and archaea for which iModulons have been calculated 20,[22][23][24][25] .…”
Section: Expanding the Usa300 Imodulons Using Rna-sequencing Data Fro...mentioning
confidence: 99%